PERLINDUNGAN HUKUM TERHADAP NASABAH ATAS KERUSAKAN ATAU KEHILANGAN BARANG JAMINAN (Studi Pada PT. Pegadaian (PERSERO) Cabang Ulak Karang Kota Padang) - Diya, Harisa (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
Based on Law Number 19 of 2003 concerning State-Owned Enterprises (BUMN),PT. Pegadaian (Persero) is a body or organization that is engaged in lending money services by mortgaging an item as collateral. As a non-bank financial institution in providing loans to the public, PT. Pegadaian (Persero) Padang City Ulak Karang Branch uses an agreement to borrow money as outlined in the form of a Pawn Certificate (SBG). Meanwhile, in handling collateral goods belonging to the customer is not always protected from damage or loss. PT. Pegadaian (Persero) The Ulak Karang Branch of Padang City has the obligation to supervise and maintain the collateral, so that the collateral does not suffer damage or loss that can harm the customer.